Links and intra-community relations through the use of protective plants: Ways to build diversity from family agroforestry systems - Furlan, Violeta; Pirondo, Analía (Ethnobotany Research and Applications, 2020)
Intra-community relationships through plants for home protection: ways to build diversity from family agroforestry systems. Background: Agroforestry systems can reflect the cultural identity of a human group. Family agroforestry systems (SAF) have shown a clear preservation of the plants that are significant for their owners. This occurs in both rural and urban settings. Each of the preserved species relates to a situated knowledge, culturally ascribed and with a particular history at a given moment. In this work, we will guide you along the paths of home protection through five plant species. These species are associated with different use histories and traditions, which intertwine in an urban environment of the Atlantic Forest and a rural one in the Wetlands of Iberá. Both areas have similar pluricultural backgrounds with influence of Guaraní traditions. The objective is to identify the plants for home protection of the region under study, as well as their meaning and function within intra-community relations. Through the plants, we will show how this intra-community relation system works. In addition, how this system is codified with plants and finally their importance in the composition of the SAF. Methods: To fulfill this objective, we conducted in-depth interviews in 40 domestic units. We worked in 20 SAF in the town of Iguazú and 20 in small villages of Iberá. Most of the interviewees were women, due to gender roles assigned to plant management locally. We collected voucher specimens of the ethnospecies mentioned by interviewees. To summarize the data we used descriptive analysis. Results: Some of the species registered are of regional importance and others known globally. Their importance associates locally as part of an intricate system of relationships, not as a good of change as considered for many other species of the SAF. Among them are plants that work as a warning, diagnosis, express bonds or rivalries among neighbors. Through five representative species of these relationships (Petiveria alliacea or “pipí”, Ruta chalepensis or “ruda”, Sansevieria spp. or “espada de San Jorge”, Dieffembachia seguine or “comigo niguém pode”, Rosmarinus officinalis or “romero”) we explain other ways to build diversity. Conclusions: Plants for home protection have an important role in both rural and urban SAF of Atlantic Forest of Argentina. Their importance relates with affective bonds among people and a system of relations with nature. Their presence in home gardens helps to maintain the health of the SAF and their components. The local importance of these plants and their meanings shows the persistence and diffusion of Guaraní traditions in the region and explains other ways of building diversity locally. Similar relationships can be studied globally to value the multiple functions that diversity fulfills. Keywords: Guaraní, nature-culture, rural, socio-ecosystems, urban